EFFECT OF AIR DRYING TEMPERATURES ON THE QUALITY OF CENTELLA ASIATICA L DRIED PRODUCTS - M. Yahya (Jurnal Teknik Mesin, 2012)
The objective of this study is to evaluate the effect of air drying temperature on the quality of Centella Asiatica L. The drying was conducted by using a constant temperature and humidity drying chamber at different drying temperatures and relative humidities (35oC, 45oC, 55oC, 65oC; 10%, 20%, 30%, 40%, 50%), respectively. Color of Centella Asiatica L was measured using a Chroma meter and the madecascosside and asiaticosside in Centella Asiatica L were identified and quantified using High Pressure Liquid Chromatography (HPLC). The results showed that the color quality of Centella Asiatica L for the drying temperature below 55oC was decreased but not significantly. The decreasing color quality was significant at temperature beyond 55oC and at higher relative humidity. This is caused by longer drying time to achieve equilibrium moisture content. The active ingredient (madecascosside and asiaticosside) in Centella Asiatica L was decreased at temperature beyond 55oC. Based on the results the quality of Centella Asiatica L can be preserved if the drying process was maintained at temperature less than 55oC. Also the results obtained from this study can be used to design a solar drying system for Centella Asiatica L and other medicinal herbs.